THE CAUSAL RELATIONSHIPS OF SERVICE MARKETING TO PERFORMANCE OF RESTAURANT ENTREPRENEURS TO SUPPORT ‘FIT’ TOURISTS WITH SERVICE QUALITY - Chompucum, Pramtip; Soonthonsmai, Vuttichat; Ingard, Apinya (CENTRAL ASIA AND THE CAUCASUS, 2022)
This study examined the consistency of structural equation modeling showing the hypothesis of the influence of service marketing mix on restaurant entrepreneurs' business performance in Thailand through service quality and empirical data. The sample group consisted of 230 entrepreneurs of small food and beverage businesses in Thailand, serving Chinese "FIT" tourists. A questionnaire was used to collect data as well as statistical analysis, mean, standard deviation, and creating a causal relationship model of service marketing mix affecting the business performance of restaurant entrepreneurs in Thailand through service quality with linear structural relationships. The relationship was tested at statistical significance of 0.05.The results revealed that restaurant entrepreneurs had an overall potential of their service marketing mix at a high level, had an overall level of service quality at the highest level, and had opinions on the overall performance at a high level. The hypothesis test results demonstrated that the developed model was consistent with the empirical data, and all variables can explain the variance in business performance, accounting for 55 percent. The service marketing mix had no direct influence on entrepreneurs' business performance, but the service marketing mix had an indirect influence on entrepreneurs' business performance through service quality with statistical significance at .01.